Quantitative proteomics reveals neuronal ubiquitination of Rngo/Ddi1 and several proteasomal subunits by Ube3a, accounting for the complexity of Angelman syndrome - Ramirez, Juanma; Lectez, Benoit; Osinalde, Nerea; Sivá, Monika; Elu, Nagore; Aloria, Kerman; Procházková, Michaela; Perez, Coralia; Martínez-Hernández, Jose; Barrio, Rosa; Šašková, Klára Grantz; Arizmendi, Jesus M; et al. (Human molecular genetics, 2018)
Angelman syndrome is a complex neurodevelopmental disorder caused by the lack of function in the brain of a single gene, UBE3A. The E3 ligase coded by this gene is known to build K48-linked ubiquitin chains, a modification historically considered to target substrates for degradation by the proteasome. However, a change in protein abundance is not proof that a candidate UBE3A substrate is indeed ubiquitinated by UBE3A. We have here used an unbiased ubiquitin proteomics approach, the bioUb strategy, to identify 79 proteins that appear more ubiquitinated in the Drosophila photoreceptor cells when Ube3a is over-expressed. We found a significantly high number of those proteins to be proteasomal subunits or proteasome-interacting proteins, suggesting a wide proteasomal perturbation in the brain of Angelman patients. We focused on validating the ubiquitination by Ube3a of Rngo, a proteasomal component conserved from yeast (Ddi1) to humans (DDI1 and DDI2), but yet scarcely characterized. Ube3a-mediated Rngo ubiquitination in fly neurons was confirmed by immunoblotting. Using human neuroblastoma SH-SY5Y cells in culture, we also observed that human DDI1 is ubiquitinated by UBE3A, without being targeted for degradation. The novel observation that DDI1 is expressed in the developing mice brain, with a significant peak at E16.5, strongly suggests that DDI1 has biological functions not yet described that could be of relevance for Angelman syndrome clinical research.
Keywords: ubikvitinligasy; Photoreceptor Cells; Humans; ubikvitinace; regulace genové exprese; Proteomics; fotoreceptory; Saccharomyces cerevisiae - proteiny; Drosophila Proteins; lidé; zvířata; neurony; myši; Ubiquitin-Protein Ligases; proteomika; Angelman Syndrome; Mice; Saccharomyces cerevisiae Proteins; proteiny Drosophily; Gene Expression Regulation; Ubiquitination; Neurons; Aspartic Acid Proteases; Drosophila; Animals; Angelmanův syndrom; aspartátové proteasy